Regionalisation and regional policy of Montenegro - Fabris Nikola; Žugić Radoje (Zbornik Radova: Geografski institut "Jovan Cvijić", 2012)
Although being a relatively small country, Montenegro is characterized by significant regional disparities. Just recently it has been administratively divided into regions, but no form of regional statistics has been developed yet and no active policy aimed at reducing regional disparities is being followed. This is due to the longstanding sentiment that the entire Montenegro is one micro region and no further division into regions is necessary. This is why the authors set three goals in writing this paper. The first one is to review the adequacy of the proposed division into regions. The second goal is to calculate relevant regional statistical indicators that would subsequently serve for the third goal of proposing economic policy recommendations aimed at diminishing regional differences.